The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1099/0022-1317-64-10-2191
|View full text |Cite
|
Sign up to set email alerts
|

Stabilities of Avian Sarcoma Virus RNAs: Comparison of Subgenomic and Genomic Species with Cellular mRNAs

Abstract: SUMMARYThe stabilities of B77 avian sarcoma virus intracellular RNAs were compared to the stability of the total cellular poly(A)-containing RNA by labelling infected chicken embryo fibroblasts with [3H]uridine for 15 h, adding actinomycin D (1 ~tg per ml) to block further transcription of viral RNA, and selecting virus-specific RNA from the total cellular poly(A)-containing RNA at 3 hourly intervals. The three virus-specific RNA species (9-3, 3.3 and 5.4 kilobases) decayed with half-lives of 7-5, 10, and 15 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
14
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
7
14
0
Order By: Relevance
“…Instead HIV-1 unspliced RNA constitutes a single functional pool that can function interchangeably as mRNA and as vpRNA. Our results are similar to results with ASV and RSV in which Stoltzfus et al (23) and Sonstegard and Hackett (22) concluded that a single metabolic pool of viral RNA exists that functions as both mRNA and vpRNA. Contrasting results in the MLV system suggested that there are two nonequilibrating pools of MLV RNA, each functioning as either mRNA or vpRNA (11).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Instead HIV-1 unspliced RNA constitutes a single functional pool that can function interchangeably as mRNA and as vpRNA. Our results are similar to results with ASV and RSV in which Stoltzfus et al (23) and Sonstegard and Hackett (22) concluded that a single metabolic pool of viral RNA exists that functions as both mRNA and vpRNA. Contrasting results in the MLV system suggested that there are two nonequilibrating pools of MLV RNA, each functioning as either mRNA or vpRNA (11).…”
Section: Discussionsupporting
confidence: 91%
“…These data implied that MLV transcripts segregate into two functionally distinct populations of mRNA for translation or vpRNA for encapsidation (11). Stoltzfus et al (23) applied isotopic equilibrium assay to cells infected with avian sarcoma virus (ASV) and observed not two but rather a single RNA population that functions as both ASV mRNA and vpRNA. Sonstegard and Hackett (22) came to similar conclusions in their studies of Rous sarcoma virus (RSV) vector RNAs.…”
mentioning
confidence: 99%
“…It is possible that U6 snRNA associates with multiple sites on the RSV genome. Evidence that RSV virion RNA can be translated prior to packaging (Stoltzfus et al 1983; J. LeBlanc and K. Beemon, unpubl. ) suggests that U6 snRNA is not associated with the efficiently translated leader region or the gag gene.…”
Section: Discussionmentioning
confidence: 99%
“…Through actD treatment of cells containing radiolabeled RNAs, Stoltzfus et al (44) determined the half-life of unspliced RSV RNAs to be 7.5 h both in the cytoplasm and in virions. Thus, they propose that RSV also employs a single population of RNAs to serve as genomic RNAs as well as mRNAs.…”
mentioning
confidence: 99%